Parametrical T-Gate for Joint Processing of Quantum and Classic Optoelectronic Signals - Alexey Y. Bykovsky; Nikolay A. Vasiliev (J, 2023)
Unmanned network robotics is a new multidisciplinary field that involves many fields of computer networks, multi-agent systems, control theory, 5G and 6G Internet, computer security, and wireless quantum communications. Efficient conjugation of such technologies needs to design new data verification schemes for robotic agents using the advantages of quantum key distribution lines. For such schemes the joint use of known fuzzy logic parametrical <semantics>T</semantics>-gates and discrete multiple-valued logic models simplifies the application of quantum quasi-random keys. Namely, the separate regulating parameter in <semantics>T</semantics>-gates is the most convenient tool to use quantum keys in comparatively simple classical control and verification procedures that do not involve quantum logic gates.